الإتصال الأسري وإنعكاسه على التنشئة الإجتماعية للأبناء - بن علي، هناء; قواسمي، جميلة (جامعة الوادي university of eloued, 2018)
"ملخص الدراسة انطلقت هذه الدراسة من تساؤل رئيسي: - ماهي إنعكاسات الاتصال الأسري على التنشئة الإجتماعية للأبناء؟ وقد شملت الدراسة على جملة من التساؤلات الفرعية هي: - هل عدم التفاعل داخل الأسرة ينعكس سلبا على التنشئة الإجتماعية للأبناء؟ - هل يؤدي غياب الحوار داخل الأسرة إلى تنشئة إجتماعية غير سوية للأبناء؟ - هل العلاقة الأسرية المتوترة تؤثر سلبا على التنشئة الإجتماعية للأبناء؟ وقد تم الإعتماد في هذه الدراسة على المنهج الوصفي التحليلي قصد وصف وتحليل والتعرف على إنعكاسات الاتصال الأسري على التنشئة الإجتماعية للأبناء, وتفسير أسباب ذلك. حيث أجريت هذه الدراسة بمتوسطة ""مسعي أحمد بلقاسم"" بالوادي وأستخدمت فيها العينة القصدية, للمستوى رابعة متوسط والتي شملت 80 تلميذ, منهم ( 25 )ذكور و( 55 )إناث. هذه الدراسة كغيرها من الدراسات توصلت إلى نتائج التالية منها: - إن عدم قضاء أفراد الأسرة وقت طويل مع بعضهم البعض ينقص من تلاحم وتماسك الأسرة وبالتالي لا يكون هناك تفاعل جيد مما يؤدي إلى تنشئة غير سليمة للأبناء, وهذا ما توضحه لنا النسبة الغالبة من إجابات المبحوثين57.14 %. - إن إهتمام الوالدين وإنسجامهم مع الأخرين بدلا من إهتمامهم بدراسة ونتائج أبنائهم يساهم في تنشئة إجتماعيه غير سوية الأبناء, وهذا كما بينته لنا نسبة إجابات المبحوثين 56.25 %. - إن عدم فتح باب الحوار لكل أفراد الأسرة عند مناقشة المسائل الأسرية وكيفية التفاعل بين الأسرية وبطريقة سهلة وسلسة يؤدي لتنشئة غير سوية للأبناء, كما أكدته لنا نسبة إجابات المبحوثين 70 % - صعوبة أو غياب الحوار وتعرض الأبناء للضرب مؤشر نحو غياب الحوار بين أفراد الأسرة, وهذا ما تأكده لنا نسبة إجابات المبحوثين86.53 % - إن تبادل اللوم المتكرر بين الوالدين يشير إلى علاقة أسرية متوترة, كما تبينه نسبة إجابات المبحوثين66.66 % - إن حدوث المشاكل والشجارات بكثرة لعدم أداء الوالدين لواجباتهم المنزلية نحو أبناءهم يخل جوا متوترا داخل الأسرة, وكما توضحه إجابات المبحوثين بنسبة46.15 % - عدم مدح الوالدين للأبناء عند قيامهم بواجباتهم المنزلية يشير إلى وجود علاقة أسرية متوترة تأثر سلبا على التنشئة الإجتماعية للأبناء, حيث توضحه إجابات المبحوثين بنسبة 61.90 % "Summary This study was launched from a major question: What are the implications of family communication on the social upbringing of children? The study included a number of sub-questions: - Is not interaction within the family reflected negatively on the social upbringing of children? - Does the lack of dialogue within the family lead to an abnormal social upbringing of the children? - Is the tense family relationship negatively affect the social upbringing of children? In this study, the analytical descriptive approach was used to describe, analyze and identify the implications of family communication on the social upbringing of children and to explain the reasons for this. This study was carried out by the medium of ""Masaie Ahmed Belkacem"" in the El Oued, where the sample was used for the fourth intermediate level, which included 80 students, of whom 25 were males and 55 were females. This study, like other studies, has reached the following results: - The lack of family members spend a long time with each other reduces the cohesion and cohesion of the family and therefore there is no good interaction leading to the upbringing of the children, which shows us the majority of the answers of respondents 57.14%. - The parents 'interest and their harmony with others rather than their study and the results of their children contribute to the formation of an abnormal social structure, as indicated by the percentage of respondents' responses to 56.25%. - The failure to open the door to dialogue for all members of the family when discussing family issues and how to interact between the family and in an easy and smooth way leads to the formation of an abnormal children, as confirmed by the proportion of respondents answers 70% - Difficulty or absence of dialogue and subjected children to beating an indicator of the absence of dialogue between family members, and this is confirmed by the proportion of respondents answers 86.53% - The exchange of repeated blame between parents indicates a tense family relationship, as shown by the proportion of respondents answers 66.66% - The occurrence of problems and arguments frequently for the failure of parents to perform their homework towards their children upset the tense atmosphere within the family, and as indicated by the answers of respondents by 46.15% The parents 'lack of praise for their children when they perform their homework indicates a tense family relationship that negatively affected the social upbringing of the children. The respondents' answers show 61.90%.
دراسة ميدانية لعينة من تلاميذ سنة رابعة متوسط بمتوسطة مسعي أحمد بلقاسم - الوادي
مذكرة ماستر علوم إجتماعية تخصص صعوبات التعلم
Keywords: الإتصال الأسري، التنشئة الإجتماعية; Communication familiale, socialisation; Family communication, socialization